2014
DOI: 10.1016/j.bmcl.2014.10.026
|View full text |Cite
|
Sign up to set email alerts
|

Dilazep analogues for the study of equilibrative nucleoside transporters 1 and 2 (ENT1 and ENT2)

Abstract: As ENT inhibitors including dilazep have shown efficacy improving oHSV1 targeted oncolytic cancer therapy, a series of dilazep analogues was synthesized and biologically evaluated to examine both ENT1 and ENT2 inhibition. The central diamine core, alkyl chains, ester linkage and substituents on the phenyl ring were all varied. Compounds were screened against ENT1 and ENT2 using a radio-ligand cell-based assay. Dilazep and analogues with minor structural changes are potent and selective ENT1 inhibitors. No sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…The bromoazide 3 , in turn, can be obtained by reacting 1,3-dibromopropane ( 4 ) with one equivalent of sodium azide. However, even if the reaction is performed under stoichiometric conditions, it has been found that the desired product cannot be recovered (by chromatography) in yields larger than 50% [ 23 25 ]. Indeed, we verified that the reaction affords mixtures containing 3 together with the relevant diazide 5 and the unreacted starting dibromide 4 ( Scheme 3 ), in 46%, 27% and 27% yields, respectively (estimated by 1 H NMR), which is in reasonable agreement with the 2:1:1 ratio expected on the grounds of numerical simulations.…”
Section: Resultsmentioning
confidence: 99%
“…The bromoazide 3 , in turn, can be obtained by reacting 1,3-dibromopropane ( 4 ) with one equivalent of sodium azide. However, even if the reaction is performed under stoichiometric conditions, it has been found that the desired product cannot be recovered (by chromatography) in yields larger than 50% [ 23 25 ]. Indeed, we verified that the reaction affords mixtures containing 3 together with the relevant diazide 5 and the unreacted starting dibromide 4 ( Scheme 3 ), in 46%, 27% and 27% yields, respectively (estimated by 1 H NMR), which is in reasonable agreement with the 2:1:1 ratio expected on the grounds of numerical simulations.…”
Section: Resultsmentioning
confidence: 99%
“…For NBTI, a selective inhibitor of ENT1, a potency value (8.3 ± 0.3) comparable to the radioligand binding data (8.7 ± 0.02) (Supplementary Material; Table S1) as well as previously reported data was found 49 . Dilazep appeared to be approximately 10-fold more potent compared to the literature 49 and the radioligand binding data, which may be explained by the fact that dilazep is a not selective ENT1 and ENT2 inhibitor 50 . The second format also provides information on the inhibitory efficacy of ENT1 inhibitors (i.e.…”
Section: Discussionmentioning
confidence: 64%
“…A 50% hCNTs-mediated [ 18 F]FLT uptake was observed in MCF7 cells. Experiments were performed in sodium-free choline-containing buffer to block hCNTs because their function depends on the presence of free (33,35). Data in Fig.…”
Section: Discussionmentioning
confidence: 99%